1998
DOI: 10.1088/0266-5611/14/3/019
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional inversion of eddy current data for non-destructive evaluation of steam generator tubes

Abstract: Three-dimensional (3D) eddy current non-destructive evaluation of steam generator tubes is cast in a wavefield integral framework and considered from an inverse problem point of view. Three inversion algorithms based on a gradient-type iterative search are studied: the modified gradient method, an inversion via the source-type integral equation, and one based on the localized nonlinear approximation. To overcome the inherent ill-posed nature of the inversion problem, a binary constraint is enforced on the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…2.2 VIM approach for 3D scalar case as coarse model to predict the ECT signal from narrow cracks This approach is analogous to previous research conducted by Monebhurrun et al (1998a, b). These authors confirmed that accounting for only one component of electric fields, in our case the xx component of the dyadic Green function, leads to a good numerical approximation of electric fields.…”
Section: Compel 313supporting
confidence: 81%
“…2.2 VIM approach for 3D scalar case as coarse model to predict the ECT signal from narrow cracks This approach is analogous to previous research conducted by Monebhurrun et al (1998a, b). These authors confirmed that accounting for only one component of electric fields, in our case the xx component of the dyadic Green function, leads to a good numerical approximation of electric fields.…”
Section: Compel 313supporting
confidence: 81%
“…The configuration itself is taken from [13]. The tube wall is a highly conductive, non-magnetic material (Inconel 600: conductivity σ 0 = 0.98 × 10 6 Sm −1 ), and it is of internal and external radii of 9.83 and 11.1 mm, resp.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Primary eddy currents induced in the tube wall are modified by the defect. A receiving coil (Rx) sees it as a variation of voltage, or equivalently of mutual Tx-Rx impedance, which follows from the reciprocity theorem [13], [18]:…”
Section: A the Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The first group of models are numerical models such as a finite element model or integral equation models (Hoole et al 1991;Caorsi et al 1994;Monebhrrun et al 1998;Yan et al 1998;Balasubramanian et al 2001;Li et al 2001;Kim et al 2003;Arunachalam 2006;Connolly et al 2009), and although accurate, tend to be computationally expensive because the models must be solved during each iteration. Alternative forward models based on neural networks have also been proposed (Qing et al 1997;Zhang and Gupta 2000;Ramuhalli et al 2002Ramuhalli et al , 2003aJoshi 2006).…”
Section: Fault Diagnosticsmentioning
confidence: 99%